2015
DOI: 10.1111/are.12803
|View full text |Cite
|
Sign up to set email alerts
|

Environmental fate and pharmacokinetics of sulphamethazine inFenneropenaeus chinensisshrimp production systems after oral administration

Abstract: The antimicrobial sulphamethazine is widely used in aquaculture for the prevention and treatment of bacterial diseases. Residues of sulphamethazine have been detected in aquatic environments and in edible tissues of aquaculture fish and shrimps at relatively low, but detectable concentrations. Detailed information on the environmental fate and pharmacokinetics of sulphamethazine in aquaculture species is essential to predict possible ecological risks and to provide recommendations on appropriate dosages and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Till now, there is no related research on pharmacokinetic of eugenol in shrimps. Lots of pharmacokinetics studies in shrimp were related to the antibacterial agents, such as oxytetracycline in white shrimp and black tiger shrimp [ 49 , 50 ], sulfamethoxazole and enrofloxacin in Pacific white shrimp [ 19 , 51 ], sulphamethazine in Fenneropenaeus chinensis shrimp [ 52 ] and oxolinic acid in kuruma shrimp [ 53 ]. Hence, in the present study, pharmacokinetics and residue eliminations of eugenol in Pacific white shrimp were firstly investigated using GC-MS/MS.…”
Section: Discussionmentioning
confidence: 99%
“…Till now, there is no related research on pharmacokinetic of eugenol in shrimps. Lots of pharmacokinetics studies in shrimp were related to the antibacterial agents, such as oxytetracycline in white shrimp and black tiger shrimp [ 49 , 50 ], sulfamethoxazole and enrofloxacin in Pacific white shrimp [ 19 , 51 ], sulphamethazine in Fenneropenaeus chinensis shrimp [ 52 ] and oxolinic acid in kuruma shrimp [ 53 ]. Hence, in the present study, pharmacokinetics and residue eliminations of eugenol in Pacific white shrimp were firstly investigated using GC-MS/MS.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding SAs, numerous PK profile studies have been reported in various aquatic animal species, namely shrimp ( Fenneropenaeus chinensis ) [ 12 ], summer flounder ( Paralichthys dentatus ) [ 13 ], walleye ( Sander vitreus ) [ 13 ], eel ( Anguilla anguilla ) [ 14 ], rainbow trout ( Oncorhynchus mykiss ) [ 15 ], yellowtail ( Seriola quinqueradiata ) [ 15 ], Atlantic salmon ( Sdmo sahr ) [ 16 ], and penaeid shrimp ( Penaeus vannamei ) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that sulfa drugs can accumulate in this organ in Fenneropenaeus chinensis and Eriocheir sinensis (Yin et al, 2004;Zhang et al, 2005;Tang et al, 2006). Gills exhibit high drug concentration, because of their continuous contact with the systemic circulation (Sun et al, 2015). The shell that contains about 20% chitin, poly-b(1-4)-N-acetyl-D-glucosamine, which has many applications in food and pharmaceutical industrials (Percot et al, 2003), is also able to retain the drug thanks to the chelation property of chitin.…”
mentioning
confidence: 99%